Analysis of Determining Priority for Leading Agricultural Commodities in Supporting Industrial Development Planning in North Buton Regency - Alwi, La Ode; Gafaruddin, Abdul; Herdhiansyah, Dhian (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
This research aims to analyze the priority determination of selected superior agricultural commodities that support industrial development in North Buton Regency. The type of data used in this research consists of primary data and secondary data. Primary data was obtained from various respondents' statements through Focus Group Discussions (FGD), while secondary data was obtained from various literature and other references that support this research. Data analysis used in this research was through a Comparison Analysis approach based on Multicriteria decision-making (MCDM), with various criteria, namely base commodities, land suitability; economic and financial feasibility, socio-cultural feasibility; and the existence of national and regional policies. The research results show that the main priority commodities selected for food crops and secondary crops are field rice commodities, while plantation and fishery commodities are coconut and capture fisheries commodities respectively. Meanwhile, the determination of priority leading industries in North Buton Regency includes; the rice flour processing industry, food feed industry, livestock industry, VCO industry, desiccated coconut (DC) industry, charcoal/activated carbon industry, coconut fiber industry, fish processing and packing industry.